PERUBAHAN GAYA BERPAKAIAN PEREMPUAN AKIBAT KEMAJUAN TEKNOLOGI DAN GLOBALISASI SERTA IMPLIKASINYA TERHADAP PENDIDIKAN - HAFIZAH HAFIZAH (STKIP ROKANIA, 2019)
This study aims to reveal the changes and effects ofwomen's dress styles due to technological advances andglobalization and their implications for education in thepeople of Jorong Aur Kuning, Pasaman Regency, aswell as the efforts of community leaders to anticipatechanges in women's clothing styles and theirimplications for education. This type of research is atype of case study. The informant selection techniqueuses a method (purposive sampling). The results of thestudy show that: 1) changes in women's dress due totechnological advances are where Minang Kabauwomen used to wear closed clothing such as KuruangClothes now because many technological advances andglobalization of closed clothing have been abandonedby women. 2). The impact of changes in women's dressstyle due to technological advances is that it has anegative impact on (a) economic life, where womenthere behave consumptively causing conflict when thedesire to buy clothes cannot be fulfilled by the family.(b) The impact on women's morals, that women thereare increasingly following the progress of the times,clothing is already westernized. (c) low levels ofeducation make women swallow all existingtechnological advancements 3). Efforts of relatedparties in anticipating changes in dress style due totechnological advances, namely: (a). community efforts.(b). family effort. and (c). the efforts of religious leaders.